A northern light - Donnelly, Jennifer (Orlando : Harcourt, 2003)
Sixteen-year-old Mattie, determined to attend college and be a writer against the wishes of her father and boyfriend, takes a job at a hotel in 1906 where the death of a guest renews her determination to live her own life.
Includes bibliographical references (p. 387-389).
Booklist starred.
School Library Journal starred.
Wilson's Senior High School.
Young Adult
Keywords: Coming of age -- Fiction; Education -- Fiction; Farm life -- New York (State) -- Fiction; Historical fiction; Hotels, motels, etc. -- Fiction; Murder -- Fiction; Bildungsromans; Education -- Fiction; Farm life -- New York (State) -- Fiction; Historical fiction; Homicide -- Fiction; Hotels and motels -- New York (State) -- Fiction; Adirondack Mountains (N.Y.) -- Fiction; New York (State) -- History -- 20th century -- Fiction; Adirondack Mountains (N.Y.) -- Fiction; New York (State) -- History -- Fiction